Information needs of parents for acute childhood illness: determining 'what, how, where and when' of safety netting using a qualitative exploration with parents and clinicians. Issue 1 (14th January 2014) - Jones, Caroline H D; Neill, Sarah; Lakhanpaul, Monica; Roland, Damian; Singlehurst-Mooney, Hayley; Thompson, Matthew
Abstract : Objective: To explore the views of parents and clinicians regarding the optimal content, format and delivery of safety netting information for acute childhood illness. Design: Qualitative study including semistructured focus groups and interviews. Setting: First contact care settings, community centres, children's centres and nurseries in the Midlands, UK. Participants: 27 parents from a travelling community, Asian British community and white British community. Sixteen clinicians including 10 doctors and 6 nurses from a general practice surgery, an out-of-hours service and two emergency departments (paediatric and combined adult and paediatric). Results: Participants described a need for safety netting to contain information on signs and symptoms of serious and common illnesses, illness management and where and when to seek help. Resources should be basic, simple to use and contain simple symbols. A key criterion was professional endorsement of resources. Internet-based information was desired which is reliable, consistent and up-to-date. Participants described a need for different types of information: that which could be delivered during consultations, as well as more general information for parents to access before consulting a healthcare professional. Face-to-face education, written materials and digital media were suggested delivery mechanisms. Audiovisual material was preferred by families with low literacy. Participants commonly suggested internet-based and phone-based resources, but the travelling community was less comfortable with these approaches. Conclusions: A multifaceted and tailored approach to safety netting is needed so that effective resources are available for parents with varying information needs, literacy levels and ability to use information technology. We have identified key aspects of content, quality criteria, format and delivery mechanisms for safety netting information from the perspectives of clinicians and parents. Resources should be coproduced with parents and clinicians to ensure that they are valued and utilised by both groups.